2018
DOI: 10.1038/d41586-018-07431-9
|View full text |Cite
|
Sign up to set email alerts
|

When skin’s defence against pollution fails

Abstract: © 2 0 1 8 S p r i n g e r N a t u r e L i m i t e d . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Therefore, the first line of defense against air pollution is skin and mucous membranes [87][88][89] . The second line of defense against air pollution is phagocytes, antimicrobial substances, natural killer cells (NK cells), inflammation, and fever.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the first line of defense against air pollution is skin and mucous membranes [87][88][89] . The second line of defense against air pollution is phagocytes, antimicrobial substances, natural killer cells (NK cells), inflammation, and fever.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed that a single 50 mGy radiation dose was sufficient to promote local perturbations in regenerated epidermises with cellular and molecular characteristics of dysplasia and EMT, which may constitute an initial risk for the future development of carcinomas. Interestingly, this approach is directly applicable to other biomedical research domains, for example characterization of the skin's defenses and responses to pollution [37].…”
Section: Discussionmentioning
confidence: 99%
“…Over a lifetime, human beings are exposed to a million or more commercial, environmental, and occupational chemicals [1] . Even when wearing face masks to avoid inhaling airborne pollutants, people may still be exposed to air pollutants through skin absorption, which is a complex problem [2] . Personal air pollutant sampling, including air samplers and pumps, is considered highly reliable and accurate for evaluating exposure and possible health effects [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Even when wearing face masks to avoid inhaling airborne pollutants, people may still be exposed to air pollutants through skin absorption, which is a complex problem. [2] Personal air pollutant sampling, including air samplers and pumps, is considered highly reliable and accurate for evaluating exposure and possible health effects. [3,4] This manner of assessment can be used for determining safe operating exposure limits and possible health risks but does not record directly an individual's exposure.…”
Section: Introductionmentioning
confidence: 99%